A PC based measurement system for obtaining spatial information and objective room-acoustic indicators - Abdou, A.; Guy, R.W. (Canadian Acoustics, 1993)
Over the last twenty years, many subjectively relevant objective room-acoustics quantities or indicators for evaluating the acoustical quality of an enclosure have been introduced. Whilst indicators give new insight into the acoustical goodness of a receiver position, there is still a need to quantitatively establish the extent that they are influenced by the interior physical features of the enclosure. The relationship between objective room-acoustic indicators and details of enclosure design from the point view of cause and effect are not fully understood; in order to contribute knowledge in this area, quality indicators must be obtained with directional information. A PC based multiple channel measurement system under current development and designed to meet these demands is presented. The system involves software developments together with hardware interfacing. Its potential is discussed and example results are given